2018
DOI: 10.1016/j.jtho.2018.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Tyrosine Kinase Fusions and BRAF Kinase Fusions are Rare but Actionable Resistance Mechanisms to EGFR Tyrosine Kinase Inhibitors

Abstract: RTK and BRAF fusions are rare but potentially druggable resistance mechanisms to EGFR TKIs. Detection of RTK and BRAF fusions should be part of comprehensive profiling panels to determine resistance to EGFR TKIs and direct appropriate combination therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 41 publications
(46 reference statements)
5
104
0
1
Order By: Relevance
“…However, both of these cases, as well as similar cases in which the FGFR3 fusion was detected in tissue or circulating tumor DNA after administration of an EGFR TKI but was not found in the pretreatment sample, have been described previously. 26 This adds to emerging data that support FGFR alterations not only as a primary driver mutation but also as a potential mechanism of resistance to other targeted agents. Terai et al developed human NSCLC lines resistant to the EGFR TKI gefitinib and showed (after confirming the absence of the T790M mutation) that there was significantly increased expression of FGFR1 compared with that in the parent nonresistant cells.…”
Section: Discussionmentioning
confidence: 80%
“…However, both of these cases, as well as similar cases in which the FGFR3 fusion was detected in tissue or circulating tumor DNA after administration of an EGFR TKI but was not found in the pretreatment sample, have been described previously. 26 This adds to emerging data that support FGFR alterations not only as a primary driver mutation but also as a potential mechanism of resistance to other targeted agents. Terai et al developed human NSCLC lines resistant to the EGFR TKI gefitinib and showed (after confirming the absence of the T790M mutation) that there was significantly increased expression of FGFR1 compared with that in the parent nonresistant cells.…”
Section: Discussionmentioning
confidence: 80%
“…Rarely, epithelial-to-mesenchymal transition can occur [67]. Other rare mechanisms of resistance to EGFR-TKIs include acquired receptor tyrosine kinase fusions and BRAF kinase fusions [68][69][70].…”
Section: Mechanisms Of Resistance To First-and Second-generation Egfrmentioning
confidence: 99%
“…Use of in situ assays can permit visualization of the compartments containing these alterations and determine if multiple events represent the collision of two independent clones or, in the case of acquired resistance following TKI therapy, induction of an oncogenic bypass pathway. 32 FISH testing can additionally enumerate the number of copies of genetic regions at a cellular level, thus it remains a gold standard for detection of both amplification events and deletion events in several clinical indications. Clinical examples will be provided in the upcoming sections.…”
Section: The Role For In Situ Testsmentioning
confidence: 99%